2006
DOI: 10.1007/s10194-006-0264-8
|View full text |Cite
|
Sign up to set email alerts
|

Headache in patients with chronic obstructive pulmonary disease: effects of chronic hypoxaemia

Abstract: The frequency and characteristics of headache in patients with chronic obstructive pulmonary disease (COPD) are not clear and there are only a few studies that have assessed the relationship between chronic hypoxaemia and headache. We performed this study in order to evaluate the frequency and characteristics of headache in COPD patients. A total of 119 patients, with a mean age of 63.4 ± 8.2 years, diagnosed with moderate or severe stable COPD were included in the study. Overall 31.9% of the patients complain… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
15
1

Year Published

2006
2006
2023
2023

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(16 citation statements)
references
References 19 publications
0
15
1
Order By: Relevance
“…In a case‐control study the relative risk of COPD in patients with migraine was 1.2 8 . Furthermore, in a study of patients with moderate to severe COPD, headache, mainly of tension type, was a common problem 14 . The association between chronic bronchitis and headache demonstrated in the present study might be explained by a specific comorbidity, by common life‐style, environmental, or occupational factors 37 .…”
Section: Commentsmentioning
confidence: 47%
See 1 more Smart Citation
“…In a case‐control study the relative risk of COPD in patients with migraine was 1.2 8 . Furthermore, in a study of patients with moderate to severe COPD, headache, mainly of tension type, was a common problem 14 . The association between chronic bronchitis and headache demonstrated in the present study might be explained by a specific comorbidity, by common life‐style, environmental, or occupational factors 37 .…”
Section: Commentsmentioning
confidence: 47%
“…Furthermore, the impact of frequent headache on the association has been investigated in children 4 but not in adults. Regarding possible associations between headache and chronic obstructive pulmonary disease (COPD) there are only 2 previous clinic‐based studies indicating an association with headache 8,14 …”
mentioning
confidence: 99%
“…Several studies have used the BPI in investigating pain in different comorbidities. Some have also investigated the cutoff points of mild (0-4), moderate (5-6), and severe pain (7)(8)(9)(10). 29,39 In the present study, the mean score was 3.7 for pain intensity and 3.9 for interference.…”
Section: Characteristics Of Painmentioning
confidence: 97%
“…A qualitative study found that unrelieved pain was a problem in patients with COPD. 7 There are also papers reporting on pain-related problems in those with COPD, such as headaches 8 and discomfort in legs during activity and in respiratory muscles. 9 However, there is sparse knowledge about the intensity, location, and nature of pain in patients with COPD.…”
mentioning
confidence: 97%
“…The headache of our patient fulfilled the criteria of chronic tension headache. However, considering the underlying disorders of the patient and the associations of headaches with polycythaemia, chronic lung diseases and hypoxia as experienced at great altitude [ 38 - 42 ], a secondary headache attributed to hypoxia/hypercapnia with the phenotype of tension headache was the more likely diagnosis. Either way, therapy could only be symptomatic.…”
Section: Discussionmentioning
confidence: 99%